2020
DOI: 10.1111/pere.12342
|View full text |Cite
|
Sign up to set email alerts
|

Shake it off: The role of optimistic expectations for conflict recovery

Abstract: As recent work suggests that global, dispositional forms of optimism may be more adaptive for relationship functioning than more focused, relationship-specific forms of optimism, the current study utilized observational and daily diary data collected from newlywed couples (N = 171) to determine whether global and specific optimistic expectations would differentially predict recovery following marital conflict. We predicted that spouses higher in global optimism would exhibit greater recovery, whereas spouses h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…For example, several articles examined how individual differences may worsen or alleviate conflict's adverse relational effects over time. These articles examined how factors such as gender (Fincham, Beach, & Davila, 2007), attachment (Cooper et al, 2018), optimism (Farnish & Neff, 2020), and goals (Gere & Impett, 2018) altered the conflict-relationship quality link. For example, Cooper et al (2018) found that attachment anxiety amplified the effects of daily conflict on relationship quality, such that partners had lower relationship quality on more conflictual versus less conflictual days.…”
Section: Individual Difference Factorsmentioning
confidence: 99%
“…For example, several articles examined how individual differences may worsen or alleviate conflict's adverse relational effects over time. These articles examined how factors such as gender (Fincham, Beach, & Davila, 2007), attachment (Cooper et al, 2018), optimism (Farnish & Neff, 2020), and goals (Gere & Impett, 2018) altered the conflict-relationship quality link. For example, Cooper et al (2018) found that attachment anxiety amplified the effects of daily conflict on relationship quality, such that partners had lower relationship quality on more conflictual versus less conflictual days.…”
Section: Individual Difference Factorsmentioning
confidence: 99%